Relación de costos y gastos con la rentabilidad de la Empresa Davis Language Solutions de la ciudad de Guayaquil entre el 2do y 3er trimestre del 2024. - Vera Caballero, María Del Carmen (2024)
This research study examines how the relationship between costs and expenses influences the profitability of the company Davis Language Solutions in the city of Guayaquil between the 2nd and 3rd quarter of 2024, which faces the absence of a systematic analysis, which enables the identification of quantitative and qualitative relationships between costs, as well as expenses in the incidence of profitability indicators, the research adopts a mixed approach, with a descriptive and exploratory type of research, involves theoretical methods such as analytical - synthetic and inductive - deductive, the SPSS statistical program, financial analysis techniques such as vertical analysis, horizontal analysis, calculation of profit margins, correlation analysis, surveys and interviews with the personnel working in the institution involved, based on a questionnaire with open and closed questions as an instrument, which were applied to a sample that considers the entire population such as the owner manager and the 5 employees of the company Davis Language Solutions, concluding that profitability is related to the management of costs and expenses, that operating costs, including salaries, advertising and While services were not always aligned with profitability projections, the reduction of certain unnecessary expenditures, along with the optimization of internal processes, contributed to strengthening the company's profit margins, highlighting the importance of strategic financial management. Finally, external factors, such as competition in the language services market and the local economy, impacted the company's profitability during the period analyzed.